Dynamics of exciton energy renormalization in monolayer transition metal disulfides - Zhao, Jiaxin (2020)
Fundamental understandings on the dynamics of charge carriers and excitonic quasiparticles in semiconductors are of central importance for both many-body physics and promising optoelectronic and photonic applications. Here, we investigated the carrier dynamics and many-body interactions in two-dimensional (2D) transition metal dichalcogenides (TMDs), using monolayer WS2 as an example, by employing femtosecond broadband pump-probe spectroscopy. Three time regimes for the exciton energy renormalization are unambiguously revealed with a distinct red-blue-red shift upon above-bandgap optical excitations. We attribute the dominant physical process in the three typical regimes to free carrier screening effect, Coulombic exciton–exciton interactions and Auger photocarrier generation, respectively, which show distinct dependence on the optical excitation wavelength, pump fluences and/or lattice temperature. An intrinsic exciton radiative lifetime of about 1.2 picoseconds (ps) in monolayer WS2 is unraveled at low temperature, and surprisingly the efficient Auger nonradiative decay of both bright and dark excitons puts the system in a nonequilibrium state at the nanosecond timescale. In addition, the dynamics of trions at low temperature is observed to be significantly different from that of excitons, e.g., a long radiative lifetime of ~ 108.7 ps at low excitation densities and the evolution of trion energy as a function of delay times. Our findings elucidate the dynamics of excitonic quasiparticles and the intricate many-body physics in 2D semiconductors, underpinning the future development of photonics, valleytronics and optoelectronics based on 2D semiconductors.